Regulation, conflict and violence in the South African minibus-taxi industry : observations from the Western Cape - Jefthas, Diane (Institute of Criminology, 2014)
This research attempts to explore the complexities of the issues underlying the instability in the South African minibus-taxi industry. Presented in this dissertation is a detailed account of the growth and development of the industry and the conflict and violence that has plagued it since the late 1980s. A review of the apartheid government's attempts to address the problems in the taxi industry, is followed by an examination of the democratic government's strategies to bring about the industry's stability through transformation, formalisation and regulation. Of particular interest is the nature of the relationships that exist both within the taxi industry and between the industry and government, more specifically, law enforcement agencies. The challenges facing future regulation of the industry are then highlighted.